Structure Design and Stepping Characteristics Analysis of the Biaxial Piezoelectric Actuated Stage Using a Thin-Disc Piezoelectric Actuator - Shann-Chyi Mou (Advances in Mechanical Engineering, 2014)
In this paper, a novel thin-disc piezoelectric actuator, 4-9-9-14 piezoelectric actuator, is used to construct and drive the micro/nanometer level biaxial piezoelectric actuated stage. The 4-9-9-14 piezoelectric actuator offers a better balanced capability of forward rotation and reverse rotation than the conventional edge-driving piezoelectric actuator. The biaxial piezoelectric actuated stage structure comprises a base, a V-shaped guide rail, an optical scale measurement system, a preload adjusting structure, and a load-carrying stage. The movement signals of the piezoelectric actuated stage are read and analyzed by means of NI PCI-6115 data acquisition card and LabVIEW software operating in conjunction with a linear optical scale. The new consideration of tuning T on time is used in place of the traditional method of changing the magnitude of driving voltage to control the stepping distance of the stage. A combined driving signal is based on the sum of a continuous driving signal for T on time and a DC signal for T on time; the combined driving signal is continuously output in this manner to form a continuous driving pulse chain. Under a constant driving voltage, the displacement of the stage increases with T on time and the displacement of the stage decreases with T on time.